Catalytic enantioselective alkylation of 2-alkoxy-tetrahydrofurans. Issue 16 (13th July 2020) - Liu, Xuan; Sun, Shaofa; Wang, Gang; Bai, Zhushuang; Pang, Jingxiang; Liu, Lei
Abstract : A nickel(ii )-catalyzed asymmetric alkylation of non-resonance-stabilized oxocarbenium ions with carboxylic acid derivatives on a large scale has been disclosed. Abstract : Catalytic asymmetric addition to non-resonance-stabilized oxocarbenium ions has remained a formidable challenge. Herein, we disclosed a nickel(ii )-catalyzed asymmetric alkylation of non-resonance-stabilized, five-membered oxocarbenium ions generated in situ from 2-alkoxy tetrahydrofurans with a broad range of carboxylic acid derivatives. The reaction exhibits high efficiency, excellent enantioselectivity, and good functional group tolerance, and can be conducted on a large scale. Aside from five-membered oxocarbenium ions, six-membered and acyclic aliphatic species were also well tolerated with excellent enantiocontrol, thus providing a practical and robust method to access enantiopure α-alkyl substituted saturated ethers.